PENGARUH TINGKAT SUKU BUNGA BANK INDONESIA DAN NILAI TUKAR RUPIAH TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN DI BEI TAHUN 2013-2015 - Mohammad Arif Efendi; Ronny Malavia Mardani (UNIVERSITAS ISLAM MALANG, 2018)
AbstractThis research method uses quantitative methods. Based on the philosophy of positivism. The sample used in this study is the value of interest rates and rupiah exchange rates with the highest and lowest share prices in banking companies listed on the Indonesia Stock Exchange in 2013-2015.SBI has a significant positive effect on stock prices. This shows that the increase in Bank Indonesia interest rates will have an impact on increasing stock prices. EXCHANGE has a significant negative effect on stock prices. This shows that the increase in KURS will have an impact on the decline in stock prices and vice versa.Keywords: Interest Rates and Exchange Rates.